Transparent marine antifouling coating with high mechanical stability as well as preparation method and application thereof
By applying the combined technology of epoxy-siloxane hybrid modification nanocellulose and acrylic-eugenol copolymer on marine optical instruments, the problem of performance degradation caused by biological pollution in marine optical instruments is solved, and an anti-fouling coating with high mechanical stability, transparency, hydrophobicity and anti-fouling performance is achieved, which is suitable for anti-fouling applications of marine optical instruments.
Patent Information
- Application Number
- CN202510172011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-17
AI Technical Summary
The prior art is difficult to effectively solve the problem of performance degradation caused by biological contamination during use of marine optical instruments, especially in terms of mechanical complexity and negative environmental impacts.
The nanocellulose is modified by epoxy-siloxane hybridization to prepare hydrophobically modified nanocellulose, and acrylic-eugenol copolymer is prepared by a one-step free radical polymerization method. Combined with these materials, and then coated onto the surface of the substrate to form a transparent marine antifouling coating with high mechanical stability.
It significantly improves the mechanical stability, transparency, hydrophobicity and anti-fouling properties of anti-fouling coatings, extends the maintenance cycle of marine facilities, reduces maintenance costs, and maintains good performance in the marine environment.
Smart Images

Figure CN119875457A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of marine antifouling, and relates to a transparent marine antifouling coating with high mechanical stability, a preparation method and use thereof. Background Art
[0002] As people pay more attention to the development of marine resources, the demand for long-term marine optical instruments such as water quality monitoring instruments and underwater cameras is increasing. Biofouling is a common problem that affects the performance of marine optical instruments during their use. Organisms, including tiny bacteria, algae, diatoms, and even the larvae of larger invertebrates, can quickly colonize their optical windows / sensors in the marine environment. Biofouling on optical windows can reduce the data quality of marine monitoring instruments and cause blurred images due to the coverage of underwater camera optical windows by biofilm. Therefore, there is an urgent need to develop biofouling control strategies for marine optical instruments.
[0003] In order to solve the problem of biofouling of marine optical instruments in marine environments, many methods have been proposed, such as mechanical methods, chemical methods, and photocatalytic methods. The mechanical wiper method is a typical mechanical technology that has been used to reduce biofouling of optical instruments in coastal environments. It is effective in keeping the optical windows clean, but the complexity of the machinery is generally considered to be its weakness. Biocide generation systems that release copper ions or tributyltin are commercial chemical strategies for biofouling control of marine optical instruments. However, their negative impact on the environment has hindered practical applications. Photocatalytic materials have been widely reported as a potential biofouling control method, but these materials are only effective within a depth of one meter. Therefore, it is of great significance to develop a reliable antifouling technology for marine optical instruments. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a transparent marine antifouling coating with high mechanical stability, a preparation method and use thereof. The preparation method provided by the present invention constructs a stable and uniform structure from a microscopic level, and achieves the excellent performance of the transparent marine antifouling coating in terms of mechanical stability, transparency, hydrophobicity and antifouling performance, thereby providing a very valuable antifouling coating for the field of marine antifouling, and has broad prospects in practical applications.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a transparent marine antifouling coating with high mechanical stability, the preparation method comprising:
[0007] (I) dispersing phosphorylated nanocellulose in ethanol to obtain a cellulose dispersion, adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid to the cellulose dispersion, mixing and stirring, and heating to react, and after the reaction is completed, rotary evaporation is performed to obtain hydrophobically modified nanocellulose;
[0008] (II) dissolving eugenol and a chain extender in a solvent, mixing and stirring at low temperature to obtain a mixed solution, adding methacryloyl chloride to the mixed solution for reaction, and filtering, adsorbing and evaporating after the reaction to obtain eugenol methacrylate monomer;
[0009] (III) dropping the eugenol methacrylate monomer, acrylate monomer and initiator obtained in step (II) into a solvent, mixing, stirring and heating to react, thereby obtaining an acrylic acid-eugenol copolymer;
[0010] (IV) The hydrophobically modified nanocellulose obtained in step (I) and the acrylic acid-eugenol copolymer obtained in step (III) are uniformly mixed to obtain a coating liquid, the coating liquid is applied to the surface of a substrate, and after drying, the transparent marine antifouling coating with high mechanical stability is obtained on the surface of the substrate.
[0011] The present invention prepares hydrophobically modified nanocellulose by epoxy-siloxane hybrid modification of nanocellulose; then, eugenol methacrylate monomer is prepared, and then acrylic acid-eugenol copolymer is prepared by a one-step free radical polymerization method; finally, the hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer are blended and coated on the surface of the substrate, and a transparent marine antifouling coating with high mechanical stability is obtained after curing at room temperature. The preparation method provided by the present invention constructs a stable and uniform structure from a microscopic level, greatly improves the mechanical stability, transparency, hydrophobicity and antifouling performance of the antifouling coating, provides a very valuable antifouling coating for the field of marine antifouling, and has broad prospects in practical applications.
[0012] In terms of mechanical stability, the present invention disperses phosphorylated nanocellulose in ethanol, adds 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid, mixes and stirs, heats and reacts, and then evaporates to obtain hydrophobically modified nanocellulose. The surface of nanocellulose fibrils is rich in hydroxyl groups, which not only gives nanocellulose rich chemical functions, enabling it to participate in subsequent chemical reactions; and the crystalline arrangement of cellulose chains gives nanocellulose excellent mechanical properties, providing mechanical support for the entire antifouling coating. The chemical reaction between the hydroxyl groups of phosphorylated nanocellulose and silane is relatively easy, and the pre-hydrolyzed silane can be easily adsorbed on the fiber surface of phosphorylated nanocellulose, and a condensation reaction occurs under thermal activation conditions to form a covalent bond. The formation of this covalent bond not only realizes the hydrophobic modification of phosphorylated nanocellulose, but also makes it a hardening and toughening phase in an organic-inorganic hybrid glass matrix, greatly improving the dispersibility of phosphorylated nanocellulose in acrylic acid-eugenol copolymer, and significantly improving the mechanical stability of the antifouling coating. After multiple wear, the water contact angle of the antifouling coating will not be greatly reduced. In addition, the high strength and toughness of phosphorylated nanocellulose can resist damage from external forces like a solid skeleton when the antifouling coating is worn, maintaining the overall structural integrity of the antifouling coating. At the same time, the hydrophobically modified nanocellulose is tightly combined with the acrylic acid-eugenol copolymer to form an effective barrier. When the antifouling coating is worn, this structure can effectively prevent water molecules from penetrating into the interior of the antifouling coating, avoiding changes in the chemical composition and physical structure of the surface of the antifouling coating, thereby ensuring that the water contact angle of the antifouling coating remains relatively stable and maintains good hydrophobic properties.
[0013] In terms of transparency, the present invention dissolves eugenol and a chain extender in a solvent, mixes and stirs at low temperature, then adds methacrylic chloride to react, and obtains eugenol methacrylate monomer by filtering, adsorption and evaporation. Among them, eugenol not only has antiseptic, antibacterial and insecticidal properties, but also can be photolyzed and biodegraded in the environment, is non-toxic and harmless, and effectively improves the antifouling performance of the antifouling coating as a bactericide, and the chemical structure and properties of eugenol have no negative impact on the transparency of the antifouling coating. In the subsequent process of forming an acrylic acid-eugenol copolymer, the molecular structure of the reaction product is regular, and no large particle agglomerates or uneven structures that can cause light scattering are produced. At the same time, the hydrophobically modified nanocellulose can be evenly distributed in the entire coating system during dispersion and mixing with the acrylic acid-eugenol copolymer, and will not hinder the transmission of light due to problems such as agglomeration, so that the antifouling coating finally formed can maintain good light transmission performance to the maximum extent and achieve high transparency. This is crucial for the application of antifouling coatings in marine environments. For example, in marine observation equipment, transparent parts of ships, etc., high-transparency antifouling coatings can effectively prevent the attachment of marine organisms without affecting the equipment's observation of the marine environment and the ship's field of vision.
[0014] In terms of hydrophobicity, the present invention disperses phosphorylated nanocellulose in ethanol during the preparation process, and reacts with a specific silane reagent to obtain hydrophobically modified nanocellulose. The hydroxyl groups on the surface of the nanocellulose fibrils react chemically with silane, and the covalent bonds formed not only realize the hydrophobic modification of the nanocellulose, but also enable it to build a stable hydrophobic structure in an organic-inorganic mixed glass matrix. When the hydrophobically modified nanocellulose is mixed with an acrylic acid-eugenol copolymer to form a coating liquid and coated with a dry film, this structure further strengthens the hydrophobicity. From a microscopic perspective, the hydrophobic functional groups are arranged in an orderly manner on the surface of the antifouling coating, forming a repellent layer for water molecules. When water contacts the antifouling coating, it is difficult for water molecules to infiltrate the surface of the antifouling coating, so that the antifouling coating has a higher water contact angle. In practical applications, since most marine organisms tend to attach to moist, hydrophilic surfaces, the high hydrophobicity of the antifouling coating can effectively reduce the erosion of the antifouling coating by seawater, reduce the probability of marine organisms attaching to the surface of the antifouling coating, and make it difficult for marine organisms to find suitable attachment conditions.
[0015] In terms of antifouling performance, the introduction of eugenol is a key factor in improving the antifouling performance of antifouling coatings. Eugenol has antiseptic, antibacterial and insecticidal properties. In the marine environment, it can effectively inhibit the growth and reproduction of marine microorganisms, algae and small marine organisms. Its non-toxic and degradable properties ensure that while playing an antifouling role, it will not cause pollution to the marine ecological environment. In the coating system, eugenol participates in the reaction in the form of eugenol methacrylate monomers, and the formed acrylic acid-eugenol copolymer is evenly distributed in the antifouling coating, continuously releasing eugenol components with antifouling activity, forming a chemical defense barrier for marine organisms in the surrounding environment. In addition, the mechanical stability and hydrophobicity of the antifouling coating also complement the antifouling property. The mechanical stability ensures that the structure of the antifouling coating remains intact during long-term use, even if it is subjected to complex external forces in the marine environment, such as seawater scouring and wave impact, and will not be damaged to cause the loss of antifouling components or reduce the antifouling effect. The hydrophobicity reduces the attachment of marine organisms from a physical level, and together with the chemical antifouling effect of eugenol, it constructs a dual antifouling mechanism, greatly enhancing the antifouling performance of the antifouling coating, extending the maintenance cycle of marine facilities, and reducing maintenance costs. It has important application value in the field of marine engineering.
[0016] As a preferred technical solution of the present invention, in step (I), the solid content of the phosphorylated nanocellulose is 0.1-1wt%, for example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional examples, the ratio of the phosphorylated nanocellulose to ethanol is 1g:(20-30)mL, for example, it can be 1g:20mL, 1g:21mL, 1g:22mL, 1g:23mL, 1g:24mL, 1g:25mL, 1g:26mL, 1g:27mL, 1g:28mL, 1g:29mL or 1g:30mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In some optional examples, the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid in the cellulose dispersion is (1-10):(15-40):(5-20):(0.1-1), for example, it can be 1:15:5:0.1, 2:18:6:0.2, 3:20:7:0.3, 4:22:8:0.4, 5:24:9:0.5, 6:26:10:0.6, 7:28:11:0.7, 8:30:12:0.8, 9:32:13:0.9, 10:34:15:1, 3:36:16:0.3, 5:38:18:0.5 or 6:40:20:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] The present invention particularly limits the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid in the cellulose dispersion to (1-10):(15-40):(5-20):(0.1-1).
[0020] The silyl group (-OCH 3 ) will be hydrolyzed to generate silanol groups (-SiOH) under the catalysis of dilute hydrochloric acid, and the silanol groups will then undergo condensation reaction with the hydroxyl groups on the surface of phosphorylated nanocellulose to form stable covalent bonds, thereby achieving hydrophobic modification of nanocellulose.
[0021] When the dosage of 3-glycidyloxypropyltrimethoxysilane is too high, the excess 3-glycidyloxypropyltrimethoxysilane will make the concentration of silanol groups in the reaction system too high, which will lead to excessive condensation between silanol groups. The excessive condensation between silanol groups will form an overly dense siloxane network structure around nanocellulose. On the one hand, this overly dense network structure will wrap part of the nanocellulose, hindering its uniform mixing with the subsequent acrylic acid-eugenol copolymer, affecting the overall structural stability and performance of the antifouling coating. On the other hand, the network structure formed by excessive condensation will produce internal stress. When the antifouling coating is subjected to the external environment (such as temperature changes, mechanical stress, etc.), the internal stress is easy to cause the antifouling coating to crack, fall off and other problems, reducing the mechanical stability of the antifouling coating. In addition, too much 3-glycidyloxypropyltrimethoxysilane will cause the hydrophobic functional groups on the coating surface to be unevenly distributed, and the hydrophobic functional groups in some areas will be too dense. Although it will improve the local hydrophobicity to a certain extent, from an overall perspective, it will destroy the hydrophobic uniformity of the antifouling coating surface, which is not conducive to improving the hydrophobic performance of the antifouling coating.
[0022] When the dosage of 3-glycidyloxypropyltrimethoxysilane is too low, the 3-glycidyloxypropyltrimethoxysilane participating in the reaction is insufficient, and the hydroxyl groups on the surface of nanocellulose cannot fully react with it, resulting in too few hydrophobic functional groups on the surface of nanocellulose, making the degree of hydrophobic modification of nanocellulose insufficient, and unable to effectively reduce the polarity of the surface of nanocellulose, thereby affecting the hydrophobicity of the entire antifouling coating. In practical applications, insufficient hydrophobicity can cause seawater to more easily infiltrate the surface of the antifouling coating, increase the possibility of marine organism attachment, and reduce the antifouling performance of the antifouling coating. In addition, due to the small amount of 3-glycidyloxypropyltrimethoxysilane combined with the surface of nanocellulose, the hardening and toughening phases formed in the organic-inorganic hybrid glass matrix are also reduced accordingly, and the mechanical stability of the antifouling coating cannot be fully improved. When the antifouling coating is worn, due to the lack of sufficient support of hydrophobically modified nanocellulose, the structure of the antifouling coating is easily destroyed, and the water contact angle will decrease to a large extent, further reducing the hydrophobicity and antifouling performance of the antifouling coating.
[0023] In some optional examples, the mass fraction of the dilute hydrochloric acid is 5 to 8wt%, for example, it can be 5.0wt%, 5.2wt%, 5.4wt%, 5.6wt%, 5.8wt%, 6.0wt%, 6.2wt%, 6.4wt%, 6.6wt%, 6.8wt%, 7.0wt%, 7.2wt%, 7.4wt%, 7.6wt%, 7.8wt% or 8.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] As a preferred technical solution of the present invention, in step (I), the heating temperature is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional examples, the heating time is 6 to 12 hours, for example, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional examples, the rotary evaporation temperature is 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In some optional examples, the rotary evaporation time is 3 to 6 hours, for example, it can be 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours, 5.5 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] As a preferred technical solution of the present invention, in step (II), the mass ratio of the eugenol to the solvent is 1:(5-10), for example, it can be 1:5.0, 1:5.5, 1:6.0, 1:6.5, 1:7.0, 1:7.5, 1:8.0, 1:8.5, 1:9.0, 1:9.5 or 1:10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional examples, the temperature for mixing and stirring the eugenol, the chain extender and the solvent is 3 to 8°C, for example, 3.0°C, 3.5°C, 4.0°C, 4.5°C, 5.0°C, 5.5°C, 6.0°C, 6.5°C, 7.0°C, 7.5°C or 8.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional examples, the mixing and stirring time of the eugenol, the chain extender and the solvent is 0.5 to 1 h, for example, 0.5 h, 0.55 h, 0.6 h, 0.65 h, 0.7 h, 0.75 h, 0.8 h, 0.85 h, 0.9 h, 0.95 h or 1 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the chain extender includes triethylamine.
[0032] In some optional examples, the solvent includes any one or a combination of at least two of butanone, tetrahydrofuran, benzene, toluene, xylene, chloroform, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide.
[0033] As a preferred technical solution of the present invention, in step (II), the molar ratio of the eugenol, the chain extender and the methacryloyl chloride is 1:(1-1.5):1, for example, it can be 1:1:1, 1:1.05:1, 1:1.1:1, 1:1.15:1, 1:1.2:1, 1:1.25:1, 1:1.3:1, 1:1.35:1, 1:1.4:1, 1:1.45:1 or 1:1.5:1, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional examples, the reaction time of the methacryloyl chloride and the mixed solution is 20 to 25 hours, for example, it can be 20 hours, 20.5 hours, 21 hours, 21.5 hours, 22 hours, 22.5 hours, 23 hours, 23.5 hours, 24 hours, 24.5 hours or 25 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional examples, the reaction temperature of the methacryloyl chloride and the mixed solution is 20-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional examples, the adsorption process uses a cationic adsorption resin.
[0037] As a preferred technical solution of the present invention, in step (III), the acrylate monomers include methyl methacrylate, butyl acrylate and triisopropylsilyl methacrylate.
[0038] In some optional examples, the mass ratio of the eugenol methacrylate monomer, the methyl methacrylate, the butyl acrylate, the triisopropylsilyl methacrylate, the initiator and the solvent is (1-10):(20-60):(10-50):(10-50):(1-5):100, for example, it can be 1:20:10:10:1:100, 1:25:15:15:1.5:100, 1:30:20:2 0:2:100, 1:35:25:25:2.5:100, 1:40:30:30:3:100, 1:45:35:35:3.5:100, 1:50:40:40:4:100, 1:55:45:45:4.5:100, 1:60:50:50:5:100, 1:40:20:20:3:100, but are not limited to the listed values, other values not listed within the numerical range are also applicable.
[0039] The present invention specifically limits the mass ratio of eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, initiator and solvent to (1-10):(20-60):(10-50):(10-50):(1-5):100. When the amount of eugenol methacrylate monomer and acrylate monomer is within the range defined by the present invention, an antifouling coating with high mechanical stability, high transparency, good hydrophobicity and excellent antifouling performance can be prepared.
[0040] Under the action of the initiator, the eugenol methacrylate monomer participates in the free radical polymerization reaction, opens and connects with the double bonds of other acrylate monomers to form a long copolymer chain. When the ratio of the eugenol methacrylate monomer and other acrylate monomers is within the scope defined by the present invention, the eugenol methacrylate monomer has a significant advantage in improving the performance of the acrylic acid-eugenol copolymer finally obtained, because, on the one hand, the eugenol functional group in the eugenol methacrylate monomer molecule contains a benzene ring structure, which increases the rigidity of the molecular chain and can adjust the molecular chain structure of the acrylic acid-eugenol copolymer, so that the acrylic acid-eugenol copolymer obtained after polymerization has a higher mechanical strength and is not easy to deform and break when subjected to external force. On the other hand, eugenol has antiseptic, antibacterial and insecticidal properties. The eugenol structure is introduced into the acrylic acid-eugenol copolymer, which gives the acrylic acid-eugenol copolymer a certain antifouling function, and lays the foundation for the antifouling performance of the subsequent antifouling coating from a molecular level.
[0041] For the final antifouling coating, adding an appropriate amount of eugenol methacrylate monomer also significantly improves the various properties of the antifouling coating. In terms of mechanical stability, the acrylic acid-eugenol copolymer molecular chains formed by the participation of an appropriate amount of eugenol methacrylate monomer are intertwined to form a stable network structure, which enhances the internal binding force of the antifouling coating. When subjected to external forces such as seawater scouring and friction, it can effectively disperse stress, maintain the structural integrity of the antifouling coating, and prevent the occurrence of problems such as peeling and damage of the antifouling coating. In terms of transparency, after the eugenol methacrylate monomer participates in the polymerization reaction, the molecular structure of the acrylic acid-eugenol copolymer formed is regular, and no large particle agglomerates will be produced. When light passes through the antifouling coating, less scattering and refraction occur, ensuring the high transparency of the antifouling coating, meeting the strict requirements of marine optical instruments, ship transparent parts, etc. for transparency. In terms of hydrophobicity, the eugenol methacrylate monomer and other acrylic monomers jointly construct the microstructure of the antifouling coating, so that the hydrophobic functional groups are arranged in an orderly manner on the surface of the antifouling coating, the water contact angle of the antifouling coating is increased, and the erosion of the antifouling coating by seawater is alleviated. In terms of antifouling performance, the antibacterial and insecticidal properties of eugenol directly act on microorganisms, algae and small marine organisms in the marine environment, inhibiting their attachment and growth on the surface of the antifouling coating. It works synergistically with the high hydrophobicity of the antifouling coating to greatly reduce the moist environment on which marine organisms rely for attachment, further enhancing the antifouling effect of the antifouling coating.
[0042] When the amount of eugenol methacrylate monomer exceeds the upper limit of the range defined in the present invention, too much eugenol methacrylate monomer participating in the reaction will result in excessive rigidity of the molecular chain of the obtained acrylic acid-eugenol copolymer, poor flexibility and processing performance, and enhanced interaction between molecular chains, resulting in increased brittleness of the final antifouling coating, which is prone to cracking when subjected to external impact or temperature changes, thereby reducing the mechanical stability of the antifouling coating. In addition, excessive use of eugenol methacrylate monomer will also result in too fast a release rate of eugenol, making it impossible to achieve a long-term and stable antifouling effect, and will also affect the transparency and hydrophobicity of the antifouling coating.
[0043] When the amount of eugenol methacrylate monomer used is lower than the lower limit of the range defined in the present invention, the mechanical strength of the acrylic acid-eugenol copolymer obtained by the reaction is limited, the antifouling performance is greatly reduced, the attachment of marine organisms cannot be effectively inhibited, it is easily damaged in the marine environment, and the transparency cannot meet the actual application requirements.
[0044] In some optional examples, the dripping rate of the eugenol methacrylate monomer, the acrylate monomer and the initiator is 20 to 30 mL / min, for example, it can be 20 mL / min, 21 mL / min, 22 mL / min, 23 mL / min, 24 mL / min, 25 mL / min, 26 mL / min, 27 mL / min, 28 mL / min, 29 mL / min or 30 mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional examples, before the eugenol methacrylate monomer, the acrylate monomer and the initiator are dripped into the solvent, nitrogen is blown for 30 to 40 minutes, for example, 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 40 minutes, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, diisopropylbenzene peroxide or dimethyl azobisisobutyrate, or a combination of at least two thereof.
[0047] In some optional examples, the solvent includes any one or a combination of at least two of butanone, tetrahydrofuran, benzene, toluene, xylene, chloroform, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide.
[0048] As a preferred technical solution of the present invention, in step (III), the heating temperature for mixing and stirring the eugenol methacrylate monomer, the acrylate monomer, the initiator and the solvent is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] The present invention uses eugenol methacrylate monomer and acrylate monomer as raw materials, and reacts under the action of an initiator to generate an acrylic acid-eugenol copolymer. The polymerization reaction starts with the initiator. Under the heating condition of 80-90°C, the weak bonds in the molecule will be homolytically cleaved. Taking azobisisobutyronitrile as an example, the -N=N- bond in its molecule is broken to generate two isobutyronitrile free radicals with unpaired electrons. This process is an endothermic reaction. The specific temperature range provides the energy required for bond breaking, so that the initiator can decompose at a suitable rate and generate an appropriate amount of free radicals. If the temperature is too high, the decomposition rate of the initiator is too fast, and a large amount of free radicals are generated instantly, which will make the reaction difficult to control; if the temperature is too low, the decomposition rate of the initiator is too slow, the amount of free radicals generated is insufficient, and the reaction is difficult to start or the rate is extremely slow. After the free radicals are generated, they will continue to react with other monomer molecules. Due to the presence of carbon-carbon double bonds in the monomer molecules, the free radicals continuously add new monomers to rapidly grow the molecular chain. In this process, the eugenol methacrylate monomer and multiple acrylate monomers in the system will randomly participate in the chain growth reaction to form a random copolymer. As the reaction proceeds, the polymer molecular chain becomes longer and longer, and the molecular weight gradually increases. During the chain growth process, temperature affects the reaction rate and the structure of the polymer. Carrying out the polymerization reaction at an appropriate temperature can ensure the smooth reaction between the reaction monomers and free radicals, so that the molecular chain grows in an orderly manner; abnormal temperature will lead to unstable chain growth rate, affecting the molecular weight distribution and structural regularity of the polymer.
[0050] Since the reaction temperature can affect the generation of free radicals and the chain growth process of the polymerization reaction, for this reason, the present invention particularly limits the mixing and stirring heating temperature of eugenol methacrylate monomer, acrylate monomer, initiator and solvent to 80-90° C. This temperature range can effectively decompose the initiator to produce free radicals, thereby initiating the free radical polymerization reaction between the monomers. At 80-90° C., the chemical bonds in the initiator (such as azobisisobutyronitrile, dibenzoyl peroxide, etc.) molecule can be broken more stably to produce free radicals at a suitable rate. These free radicals react rapidly with eugenol methacrylate monomer and acrylate monomer to initiate the chain polymerization between the monomer molecules, and gradually form acrylic acid-eugenol copolymer. In this process, suitable temperature ensures the controllability of the polymerization reaction, so that the molecular chain growth rate of the polymer is moderate, and a copolymer with a regular structure and uniform molecular weight distribution can be formed, which is crucial to the comprehensive performance improvement of the coating.
[0051] When the heating temperature exceeds 90°C, the decomposition rate of the initiator will be greatly accelerated, and too many free radicals will be generated. Excessive free radicals will cause the polymerization reaction rate to rise sharply, making the reaction difficult to control and prone to implosion. Implosion will not only broaden the molecular weight distribution of the polymer and form a large number of short chains and branched structures, but will also cause local overheating, leading to carbonization or excessive cross-linking of the polymer, making the antifouling coating brittle, reducing its flexibility, and prone to cracking when subjected to external forces. In addition, excessively high temperatures will also trigger a series of side reactions, such as thermal decomposition and oxidation reactions of monomers. These side reactions will consume monomers, reduce the effective utilization of monomers, and reduce the amount of copolymers produced, thereby affecting the various properties of the antifouling coating.
[0052] When the heating temperature is lower than 80°C, the decomposition rate of the initiator will be significantly reduced, and the number of free radicals generated will be insufficient, resulting in a slow polymerization reaction rate, and may even prevent the reaction from proceeding smoothly. On the one hand, the reaction time will be greatly extended, reducing production efficiency and increasing production costs. On the other hand, due to incomplete reaction, the generated copolymer has a low molecular weight and a short molecular chain, and cannot form a network structure of sufficient strength. In this case, the mechanical stability of the antifouling coating will be seriously affected, making it difficult for the antifouling coating to withstand external forces such as water scouring and mechanical friction in the marine environment, and prone to wear, shedding and other problems. At the same time, unreacted monomers will remain in the antifouling coating, affecting the chemical stability of the antifouling coating, causing the antifouling coating to be vulnerable to attack by corrosive media such as seawater during long-term use, thereby reducing the antifouling performance and service life of the antifouling coating.
[0053] In some optional examples, the heating time for mixing and stirring the eugenol methacrylate monomer, the acrylate monomer, the initiator and the solvent is 3 to 8 hours, for example, it can be 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours, 5.5 hours, 6.0 hours, 6.5 hours, 7.0 hours, 7.5 hours or 8.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] As a preferred technical solution of the present invention, in step (IV), the mass ratio of the hydrophobically modified nanocellulose to the acrylic acid-eugenol copolymer is (5-20):100, for example, it can be 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, 16:100, 17:100, 18:100, 19:100 or 20:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] The present invention further limits the mass ratio of the hydrophobically modified nanocellulose and the acrylic acid-eugenol copolymer to (5-20):100. The setting of this ratio has a crucial influence on the mechanical stability, transparency, hydrophobicity and antifouling performance of the coating.
[0056] In terms of mechanical stability, nanocellulose itself possesses excellent mechanical properties, and the crystal arrangement of its cellulose chain gives it higher strength and modulus. In the coating system, when the consumption of hydrophobically modified nanocellulose is within the scope defined by the present invention, hydrophobically modified nanocellulose can be closely combined with acrylic acid-eugenol copolymer to play the role of strengthening and toughening. On the one hand, hydrophobically modified nanocellulose, as a rigid filler, is dispersed in the copolymer matrix, which can enhance the overall rigidity of the coating so that it can better resist deformation when subjected to external force. On the other hand, the interaction between hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer, such as hydrogen bond, van der Waals force, etc., can effectively transfer stress, prevent the generation and expansion of cracks, and improve the mechanical stability of antifouling coating. When the consumption of hydrophobically modified nanocellulose exceeds the upper limit of the scope defined by the present invention, the agglomeration phenomenon of hydrophobically modified nanocellulose can cause stress concentration points to increase, and when subjected to external force, cracks are easily generated around the agglomerate, reducing the mechanical stability of the antifouling coating, making it more easily damaged under the conditions of wear and tear, impact, etc. When the amount of hydrophobically modified nanocellulose is lower than the lower limit of the range defined in the present invention, the strengthening and toughening effects on the antifouling coating are not obvious, the mechanical strength and toughness of the antifouling coating cannot be effectively improved, and it is difficult to withstand the complex external forces in the marine environment, such as seawater scouring, wave impact, etc.
[0057] In terms of transparency, when the amount of hydrophobically modified nanocellulose is within the range defined by the present invention, the hydrophobically modified nanocellulose can be evenly dispersed in the copolymer matrix. Due to its small size and good compatibility with the copolymer, it will not produce agglomerates of larger particles, and will not hinder the propagation of light, thereby ensuring the high transparency of the antifouling coating, ensuring the clear observation of the marine environment by the equipment and the good vision of the ship. When the amount of hydrophobically modified nanocellulose exceeds the upper limit of the range defined by the present invention, the agglomeration phenomenon will not only affect the hydrophobicity and mechanical stability of the antifouling coating, but also cause the light to be scattered and refracted during the propagation process, reducing the transparency of the antifouling coating.
[0058] In terms of hydrophobicity, when the amount of hydrophobically modified nanocellulose is within the range defined in the present invention, the hydrophobically modified nanocellulose can construct a stable hydrophobic structure in the antifouling coating, and the hydrophobic functional groups on its surface will spontaneously migrate to the surface of the antifouling coating and arrange in order during the drying and film-forming process of the antifouling coating, forming a repelling layer for water molecules, so that the antifouling coating has a higher water contact angle, and effectively alleviates the erosion of the antifouling coating by seawater. When the amount of hydrophobically modified nanocellulose exceeds the upper limit of the range defined in the present invention, too much hydrophobically modified nanocellulose will agglomerate inside the antifouling coating, destroying the orderly arrangement of the hydrophobic functional groups, and even forming defects on the surface of the antifouling coating, causing water molecules to easily penetrate into the interior of the antifouling coating, reducing the hydrophobicity of the antifouling coating. When the amount of hydrophobically modified nanocellulose is lower than the lower limit of the range defined in the present invention, a complete and effective hydrophobic structure cannot be formed, the number of hydrophobic functional groups on the surface of the antifouling coating is insufficient, the repelling effect on water molecules is weakened, the hydrophobicity is significantly reduced, and marine organisms are more likely to attach to the wet antifouling coating surface.
[0059] In terms of antifouling performance, the hydrophobicity of hydrophobically modified nanocellulose indirectly improves the antifouling performance of antifouling coating to a certain extent. When the consumption of hydrophobically modified nanocellulose is within the scope defined by the present invention, the surface hydrophobicity of antifouling coating can be significantly improved, the moist environment on which marine organisms rely for attachment is reduced, and the probability of marine organisms attaching to the surface of antifouling coating is reduced. At the same time, the synergistic effect of hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer ensures the integrity of the antifouling coating structure, so that the eugenol component in the copolymer can be released continuously and stably, and the antibacterial and insecticidal effects are exerted, and the growth and reproduction of marine microorganisms, algae and small marine organisms are inhibited. When the consumption of hydrophobically modified nanocellulose exceeds the upper limit of the scope defined by the present invention, the decline of hydrophobicity and mechanical stability will weaken the antifouling performance of antifouling coating, and the agglomeration of hydrophobically modified nanocellulose will lead to antifouling coating defects, making marine organisms more easily attached to the surface of antifouling coating. In addition, the instability of the antifouling coating structure will also accelerate the release of eugenol, and long-term antifouling cannot be achieved. When the amount of hydrophobically modified nanocellulose is lower than the lower limit of the range defined in the present invention, the antifouling coating will be insufficiently hydrophobic, the release of eugenol will also be affected, and the antifouling performance will be difficult to effectively exert.
[0060] In some optional examples, the coating method is spraying, scraping, dripping or brushing.
[0061] In some optional examples, the coating thickness of the coating liquid is 50 to 200 μm, for example, it can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional examples, the substrate is made of iron, aluminum, copper or glass.
[0063] In some optional embodiments, the drying temperature is 20-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional examples, the drying time is 4 to 8 hours, for example, 4.0 hours, 4.5 hours, 5.0 hours, 5.5 hours, 6.0 hours, 6.5 hours, 7.0 hours, 7.5 hours or 8.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In a second aspect, the present invention provides a transparent marine antifouling coating with high mechanical stability prepared by the preparation method described in the first aspect, wherein the transparent marine antifouling coating comprises hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer.
[0066] In a third aspect, the present invention provides a use of the transparent marine antifouling coating with high mechanical stability described in the second aspect, wherein the transparent marine antifouling coating with high mechanical stability is used for marine optical instruments.
[0067] Compared with the prior art, the present invention has the following beneficial effects:
[0068] The present invention prepares hydrophobically modified nanocellulose by epoxy-siloxane hybrid modification of nanocellulose; then, eugenol methacrylate monomer is prepared, and then acrylic acid-eugenol copolymer is prepared by a one-step free radical polymerization method; finally, the hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer are blended and coated on the surface of the substrate, and a transparent marine antifouling coating with high mechanical stability is obtained after curing at room temperature. The preparation method provided by the present invention constructs a stable and uniform structure from a microscopic level, greatly improves the mechanical stability, transparency, hydrophobicity and antifouling performance of the antifouling coating, provides a very valuable antifouling coating for the field of marine antifouling, and has broad prospects in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 A process flow chart of the preparation of a transparent marine antifouling coating provided in Examples 1-5 of the present invention;
[0070] Figure 2 This is a comparison chart of the mass loss rates of the transparent marine antifouling coatings prepared in Examples 1-2 of the present invention and Comparative Examples 1-3 after the sandpaper abrasion test;
[0071] Figure 3 This is a comparison chart of the transmittance of the transparent marine antifouling coatings prepared in Examples 1-4 of the present invention;
[0072] Figure 4 This is a physical picture of the transparent marine antifouling coating prepared in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0073] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0074] Example 1
[0075] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0076] (1) dispersing phosphorylated nanocellulose with a solid content of 0.1 wt% in ethanol, wherein the ratio of phosphorylated nanocellulose to ethanol is 1 g:20 mL, and obtaining a cellulose dispersion after ultrasonic dispersion; adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and 5 wt% dilute hydrochloric acid to the cellulose dispersion, wherein the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is 1:15:5:0.1, mixing and stirring at 60° C. for 12 h to react, and after the reaction is completed, rotary evaporation at 60° C. for 6 h to obtain hydrophobically modified nanocellulose;
[0077] (2) dissolving eugenol and triethylamine in xylene at a mass ratio of eugenol to xylene of 1:5, mixing and stirring at 3°C for 1 hour to obtain a mixed solution; adding methacryloyl chloride to the mixed solution at a molar ratio of eugenol, triethylamine and methacryloyl chloride of 1:1:1, reacting at 20°C for 25 hours, filtering to remove the ammonium salt produced by the reaction after the reaction, then removing the unreacted monomer with a cationic adsorption resin, and finally evaporating the xylene under low pressure to obtain eugenol methacrylate monomer;
[0078] (3) nitrogen blowing was performed on xylene for 30 minutes, and the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and azobisisobutyronitrile obtained in step (2) were dripped into the xylene at a rate of 20 mL / min, wherein the mass ratio of the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, azobisisobutyronitrile and xylene was 1:20:10:10:1:100, and the mixture was mixed and stirred at 80° C. for 8 hours to react, thereby obtaining an acrylic acid-eugenol copolymer;
[0079] (4) The hydrophobically modified nanocellulose obtained in step (1) and the acrylic acid-eugenol copolymer obtained in step (3) are mixed uniformly at a mass ratio of 5:100 to obtain a coating solution, and the coating solution is applied to the surface of the substrate with a coating thickness of 50 μm, and then dried at 20° C. for 8 h to obtain the transparent marine antifouling coating (such as Figure 4 shown).
[0080] Example 2
[0081] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0082] (1) dispersing phosphorylated nanocellulose with a solid content of 0.3 wt% in ethanol, wherein the ratio of phosphorylated nanocellulose to ethanol is 1 g:22 mL, and obtaining a cellulose dispersion after ultrasonic dispersion; adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid with a mass fraction of 6 wt% to the cellulose dispersion, wherein the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is 3:20:8:0.3, mixing and stirring at 62° C. for 10 h to react, and after the reaction is completed, rotary evaporation is performed at 70° C. for 5 h to obtain hydrophobically modified nanocellulose;
[0083] (2) dissolving eugenol and triethylamine in butanone at a mass ratio of eugenol to butanone of 1:6, and stirring at 4°C for 0.8h to obtain a mixed solution; adding methacryloyl chloride to the mixed solution at a molar ratio of eugenol, triethylamine and methacryloyl chloride of 1:1.1:1, and reacting at 22°C for 24h, filtering to remove the ammonium salt produced by the reaction after the reaction, and then removing the unreacted monomer with a cationic adsorption resin, and finally evaporating butanone under low pressure to obtain eugenol methacrylate monomer;
[0084] (3) nitrogen blowing is performed on butanone for 32 minutes, and the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and azobisisoheptanonitrile obtained in step (2) are dripped into butanone at a rate of 22 mL / min, wherein the mass ratio of eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, azobisisoheptanonitrile and butanone is 3:30:20:20:2:100, and the mixture is mixed and stirred at 82° C. for 6 hours to react, thereby obtaining an acrylic acid-eugenol copolymer;
[0085] (4) The hydrophobically modified nanocellulose obtained in step (1) and the acrylic acid-eugenol copolymer obtained in step (3) are mixed uniformly at a mass ratio of 8:100 to obtain a coating solution, and the coating solution is applied to the surface of the substrate with a coating thickness of 80 μm, and then dried at 22° C. for 7 h to obtain the transparent marine antifouling coating (such as Figure 4 shown).
[0086] Example 3
[0087] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0088] (1) dispersing phosphorylated nanocellulose with a solid content of 0.5 wt% in ethanol, wherein the ratio of phosphorylated nanocellulose to ethanol is 1 g:25 mL, and obtaining a cellulose dispersion after ultrasonic dispersion; adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid with a mass fraction of 6 wt% to the cellulose dispersion, wherein the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is 5:25:10:0.5, mixing and stirring at 65° C. for 9 h to react, and after the reaction is completed, rotary evaporation at 75° C. for 4 h to obtain hydrophobically modified nanocellulose;
[0089] (2) dissolving eugenol and triethylamine in tetrahydrofuran, wherein the mass ratio of eugenol to tetrahydrofuran is 1:7, and stirring at 5° C. for 0.7 h to obtain a mixed solution; adding methacryloyl chloride to the mixed solution, wherein the molar ratio of eugenol, triethylamine and methacryloyl chloride is 1:1.2:1, and reacting at 25° C. for 23 h. After the reaction is completed, filtering is performed to remove the ammonium salt produced by the reaction, and then unreacted monomers are removed by using a cationic adsorption resin, and finally evaporating tetrahydrofuran under low pressure to obtain eugenol methacrylate monomer;
[0090] (3) nitrogen blowing was performed on tetrahydrofuran for 35 minutes, and the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and dibenzoyl peroxide obtained in step (2) were dripped into tetrahydrofuran at a rate of 25 mL / min, wherein the mass ratio of eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, dibenzoyl peroxide and tetrahydrofuran was 5:40:30:30:3:100, and the mixture was mixed and stirred at 85° C. for 5 hours to react, thereby obtaining an acrylic acid-eugenol copolymer;
[0091] (4) The hydrophobically modified nanocellulose obtained in step (1) and the acrylic acid-eugenol copolymer obtained in step (3) are mixed uniformly at a mass ratio of 10:100 to obtain a coating solution, and the coating solution is applied to the surface of the substrate with a coating thickness of 100 μm, and then dried at 25° C. for 6 h to obtain the transparent marine antifouling coating (such as Figure 4 shown).
[0092] Example 4
[0093] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0094] (1) dispersing phosphorylated nanocellulose with a solid content of 0.7 wt % in ethanol, wherein the ratio of phosphorylated nanocellulose to ethanol is 1 g:28 mL, and obtaining a cellulose dispersion after ultrasonic dispersion; adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and 7 wt % dilute hydrochloric acid to the cellulose dispersion, wherein the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is 8:30:15:0.8, mixing and stirring at 68° C. for 8 h to react, and after the reaction is completed, rotary evaporation at 80° C. for 4 h to obtain hydrophobically modified nanocellulose;
[0095] (2) dissolving eugenol and triethylamine in N,N-dimethylformamide in a mass ratio of eugenol to N,N-dimethylformamide of 1:8, and stirring at 6° C. for 0.6 h to obtain a mixed solution; adding methacryloyl chloride to the mixed solution in a molar ratio of eugenol, triethylamine and methacryloyl chloride of 1:1.3:1, and reacting at 28° C. for 22 h. After the reaction is completed, filtering to remove the ammonium salt produced by the reaction, then using a cationic adsorption resin to remove the unreacted monomer, and finally evaporating N,N-dimethylformamide under low pressure to obtain eugenol methacrylate monomer;
[0096] (3) nitrogen blowing was performed on N,N-dimethylformamide for 38 minutes, and the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and diisopropylbenzene peroxide obtained in step (2) were dripped into N,N-dimethylformamide at a rate of 28 mL / min, wherein the mass ratio of eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, diisopropylbenzene peroxide and N,N-dimethylformamide was 7:50:40:40:4:100, and the mixture was mixed and stirred at 88° C. for 4 hours to react, thereby obtaining an acrylic acid-eugenol copolymer;
[0097] (4) The hydrophobically modified nanocellulose obtained in step (1) and the acrylic acid-eugenol copolymer obtained in step (3) are mixed uniformly at a mass ratio of 15:100 to obtain a coating solution, and the coating solution is applied to the surface of the substrate with a coating thickness of 150 μm, and then dried at 28° C. for 5 h to obtain the transparent marine antifouling coating (such as Figure 4 shown).
[0098] Example 5
[0099] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0100] (1) dispersing phosphorylated nanocellulose with a solid content of 1 wt% in ethanol, wherein the ratio of phosphorylated nanocellulose to ethanol is 1 g:30 mL, and obtaining a cellulose dispersion after ultrasonic dispersion; adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and 8 wt% dilute hydrochloric acid to the cellulose dispersion, wherein the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is 10:40:20:1, mixing and stirring at 70° C. for 6 h to react, and after the reaction is completed, rotary evaporation at 90° C. for 3 h to obtain hydrophobically modified nanocellulose;
[0101] (2) dissolving eugenol and triethylamine in dimethyl sulfoxide, wherein the mass ratio of eugenol to dimethyl sulfoxide is 1:10, and stirring the mixture at 8° C. for 0.5 h to obtain a mixed solution; adding methacryloyl chloride to the mixed solution, wherein the molar ratio of eugenol, triethylamine and methacryloyl chloride is 1:1.5:1, and reacting the mixture at 30° C. for 20 h. After the reaction is completed, filtering is performed to remove the ammonium salt produced by the reaction, and then unreacted monomers are removed by using a cationic adsorption resin, and finally dimethyl sulfoxide is evaporated under low pressure to obtain eugenol methacrylate monomer;
[0102] (3) nitrogen blowing is performed on dimethyl sulfoxide for 40 minutes, and the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and dimethyl azobisisobutyrate obtained in step (2) are dripped into dimethyl sulfoxide at a rate of 30 mL / min, wherein the mass ratio of eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, dimethyl azobisisobutyrate and dimethyl sulfoxide is 10:60:50:50:5:100, and the mixture is mixed and stirred at 90° C. for 3 hours to react, thereby obtaining an acrylic acid-eugenol copolymer;
[0103] (4) The hydrophobically modified nanocellulose obtained in step (1) and the acrylic acid-eugenol copolymer obtained in step (3) are mixed uniformly at a mass ratio of 20:100 to obtain a coating solution, and the coating solution is applied to the surface of the substrate with a coating thickness of 200 μm, followed by drying at 30° C. for 4 h to obtain the transparent marine antifouling coating (such as Figure 4 shown).
[0104] Example 6
[0105] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (1), the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is adjusted to 1:10:5:0.1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0106] Example 7
[0107] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (1), the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is adjusted to 1:45:5:0.1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0108] Example 8
[0109] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (3), the mass ratio of eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, initiator and solvent is adjusted to 0.5:20:10:10:1:100, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0110] Example 9
[0111] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (3), the mass ratio of eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, initiator and solvent is adjusted to 15:20:10:10:1:100, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0112] Example 10
[0113] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (3), the heating temperature for mixing and stirring eugenol methacrylate monomer, acrylate monomer, initiator and solvent is adjusted to 70°C, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0114] Embodiment 11
[0115] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (3), the heating temperature for mixing and stirring the eugenol methacrylate monomer, acrylate monomer, initiator and solvent is adjusted to 100° C., and the other operating steps and process parameters are exactly the same as those in Example 1.
[0116] Example 12
[0117] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (4), the mass ratio of hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer is adjusted to 1:100, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0118] Embodiment 13
[0119] This embodiment provides a method for preparing a transparent marine antifouling coating with high mechanical stability. The difference from Example 1 is that in step (4), the mass ratio of hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer is adjusted to 25:100, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0120] Comparative Example 1
[0121] This comparative example provides a method for preparing a transparent marine antifouling coating, and the preparation method specifically comprises the following steps:
[0122] (1) dissolving eugenol and triethylamine in xylene in a mass ratio of eugenol to xylene of 1:5, and stirring the mixture at 3° C. for 1 hour to obtain a mixed solution; adding methacryloyl chloride to the mixed solution in a molar ratio of eugenol, triethylamine and methacryloyl chloride of 1:1:1, and reacting the mixture at 20° C. for 25 hours. After the reaction is completed, filtering to remove the ammonium salt produced by the reaction, and then removing the unreacted monomer with a cationic adsorption resin, and finally evaporating the xylene under low pressure to obtain eugenol methacrylate monomer;
[0123] (2) nitrogen blowing was performed on xylene for 30 minutes, and the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and azobisisobutyronitrile obtained in step (1) were dripped into the xylene at a rate of 20 mL / min, wherein the mass ratio of the eugenol methacrylate monomer, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, azobisisobutyronitrile and xylene was 1:20:10:10:1:100, and the mixture was mixed and stirred at 80° C. for 8 hours to react, thereby obtaining an acrylic acid-eugenol copolymer;
[0124] (3) coating the acrylic acid-eugenol copolymer obtained in step (2) on the surface of the substrate with a coating thickness of 50 μm, and then drying at 20° C. for 8 h to obtain the transparent marine antifouling coating on the surface of the substrate.
[0125] Comparative Example 2
[0126] This comparative example provides a method for preparing a transparent marine antifouling coating, and the preparation method specifically comprises the following steps:
[0127] (1) dispersing phosphorylated nanocellulose with a solid content of 0.1 wt% in ethanol, wherein the ratio of phosphorylated nanocellulose to ethanol is 1 g:20 mL, and obtaining a cellulose dispersion after ultrasonic dispersion; adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and 5 wt% dilute hydrochloric acid to the cellulose dispersion, wherein the mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid is 1:15:5:0.1, mixing and stirring at 60° C. for 12 h to react, and after the reaction is completed, rotary evaporation at 60° C. for 6 h to obtain hydrophobically modified nanocellulose;
[0128] (2) nitrogen blowing was performed on xylene for 30 minutes, and methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and azobisisobutyronitrile were dripped into the xylene at a rate of 20 mL / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, azobisisobutyronitrile and xylene was 20:10:10:1:100, and the mixture was mixed and stirred at 80° C. for 8 hours to react, thereby obtaining an acrylic copolymer;
[0129] (3) The hydrophobically modified nanocellulose obtained in step (1) and the acrylic copolymer obtained in step (2) are mixed uniformly in a mass ratio of 5:100 to obtain a coating liquid, and the coating liquid is applied to the surface of the substrate with a coating thickness of 50 μm, and then dried at 20° C. for 8 h to obtain the transparent marine antifouling coating on the surface of the substrate.
[0130] Comparative Example 3
[0131] This comparative example provides a method for preparing a transparent marine antifouling coating, and the preparation method specifically comprises the following steps:
[0132] (1) nitrogen blowing was performed on xylene for 30 minutes, methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate and azobisisobutyronitrile were added dropwise into the xylene at a rate of 20 mL / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, triisopropylsilyl methacrylate, azobisisobutyronitrile and xylene was 20:10:10:1:100, and the mixture was mixed and stirred at 80° C. for 8 hours to react, thereby obtaining an acrylic copolymer;
[0133] (2) coating the acrylic copolymer obtained in step (1) on the surface of the substrate with a coating thickness of 50 μm, and then drying at 20° C. for 8 h to obtain the transparent marine antifouling coating on the surface of the substrate.
[0134] The water contact angle, mechanical stability, transparency, antibacterial property and anti-algae property of the antifouling coatings prepared in each embodiment and each comparative example were tested. The testing method is as follows. The test results are shown in Table 1.
[0135] (1) Water contact angle
[0136] The water contact angle was measured by a contact angle meter (Bioline Technology Co., Ltd., Sweden, model: ThetaLite), with a water drop volume of 4 μL, and the measurement was performed 5 to 15 seconds after the drop. Five points were randomly selected from each coating surface for testing, and the average of the five measurements was taken as the water contact angle value of the coating.
[0137] (2) Sandpaper wear test
[0138] The sandpaper abrasion test is the most common and effective method to evaluate the mechanical strength of antifouling coatings. Use a coated glass slide as the test sample, place the coating face down on sandpaper (240 mesh), press a 100g weight on the glass slide, then move the glass slide horizontally for 10cm, then rotate the glass slide 90° clockwise and move it horizontally for another 10cm. This process is considered a wear cycle.
[0139] First, weigh the mass of the blank glass sheet, denoted as W b Next, the coating to be tested is coated on a glass sheet using a wire rod and dried to a constant weight, which is recorded as W 0 The coating was then subjected to a sandpaper wear test and weighed after 200 wear cycles and recorded as W t , the mass loss rate (denoted as M) is calculated by the following equation.
[0140]
[0141] The changes in the water contact angle of the transparent marine antifouling coating were tested at different abrasion cycles, and the results were as follows: Figure 2 As shown in the mass loss rate comparison chart, it can be seen from the figure that with the increase of the number of wear cycles, the mass loss rate of the transparent marine antifouling coating prepared by Comparative Example 1, Comparative Example 2 and Comparative Example 3 is greatly improved, which indicates that the mechanical stability of the transparent marine antifouling coating can be greatly improved by adding hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer.
[0142] (3) Transparency test
[0143] The transmittance of the glass sample was measured in the spectral range of 400 to 800 nm using a spectrophotometer (TU-1810). Figure 3 As shown in the transmittance comparison diagram, it can be seen from the figure that at different wavelengths, the transparent marine antifouling coating prepared by the present invention has higher light transmittance.
[0144] (4) Antibacterial test
[0145] Since E. coli is commonly found in the marine environment and in daily life, the antibacterial properties of the coatings were evaluated by E. coli. Each coating was immersed in 10 ml of bacterial suspension (approximately 10 6 CFU) in a sterile culture dish and cultured at 37°C for 12 hours. After culture, rinse the coating three times with PBS buffer to remove unstable adhering bacteria and discard the rinsing solution. Subsequently, rinse the coating repeatedly to completely separate the attached bacteria and retain the rinsing solution. Spread 200 μL of the rinsing solution evenly on the LB agar culture plate and finally culture it at 37°C for another 18 hours. The antibacterial experiment was repeated three times and the average value was taken. The antibacterial rate was calculated based on the number of colonies on the plate. The antibacterial rate (R b ) is calculated as follows:
[0146]
[0147] Among them, N b and N c Refers to the number of colonies on the plates corresponding to the blank group without coating and the experimental group with coating, respectively.
[0148] (5) Anti-algae test
[0149] Nitzschiaclosterium was used to evaluate the anti-diatom adhesion performance of the coating. Nitzschiaclosterium was cultured in F / 2 medium at 25°C with a 12:12 hour light-dark cycle. The glass slide coated with the coating to be tested was placed vertically in the algae solution, so as to minimize the occurrence of diatoms depositing on the coating surface due to gravity, thereby reducing the experimental error. Three parallel experiments were performed for each group of coating samples. After the coating was soaked in the algae solution for one week, it was taken out and the diatoms that were not firmly adhered to the coating surface were gently rinsed with seawater. Then the coating was immersed in an 80wt% acetone aqueous solution to extract diatom chlorophyll. Finally, the fluorescence intensity was measured with an AMIscience chlorophyll fluorescence meter, and the anti-algae rate of the sample to be tested was calculated.
[0150] I=(1-X / Y)×100%
[0151] Wherein, I is the diatom inhibition rate; X is the fluorescence intensity of diatoms attached to the test sample; and Y is the fluorescence intensity of diatoms attached to the control sample.
[0152] (6) Actual sea hanging board test
[0153] A 90-day marine field test was conducted from September to December in the Bohai Sea, Tianjin, China (117°46′E, 39°43′N). The coating panels were mounted on stainless steel frames and immersed at a depth of 0.5m below sea level. Three replicates were used for each coating. After a period of time, the frames were removed and rinsed with natural seawater to remove unstable attached silt and biofouling. The antifouling performance of the coatings was evaluated according to the national standard GB / T5370-2007 Shallow Sea Immersion Test Method for Antifouling Paint Samples.
[0154] Table 1
[0155]
[0156]
[0157] It can be seen from the test data provided in Table 1 that the water contact angles of the antifouling coatings prepared in Examples 1-5 of the present invention are all above 101°, which are much higher than those of Comparative Examples 1-3. The larger the water contact angle, the stronger the hydrophobicity, which indicates that the hydrophobicity of the antifouling coating prepared by the preparation method provided by the present invention is better than that of the comparative example. This is due to the preparation of the hydrophobically modified nanocellulose in the examples, whose surface hydroxyl groups react with silane to form a hydrophobic structure, and are evenly distributed in the antifouling coating, thereby enhancing the hydrophobicity of the antifouling coating.
[0158] The antibacterial property of the antifouling coatings prepared in Examples 1-5 of the present invention is all above 90%, and the anti-algae rate is all above 97%, which is much higher than that of Comparative Examples 1-3. This is because eugenol has antiseptic and antibacterial properties. In the antifouling coatings prepared in the examples, eugenol methacrylate monomers are used to participate in the reaction, and the acrylic acid-eugenol copolymer formed can continuously release eugenol and inhibit the growth of Escherichia coli, making the antibacterial property of the antifouling coatings prepared in the examples more excellent. In addition, the antifouling coatings prepared in the examples also have good hydrophobicity, which is not conducive to the attachment of algae. Under the combined effect of antibacterial property and hydrophobicity, the anti-algae property of the antifouling coatings prepared in the examples is more excellent.
[0159] In the actual sea hanging board test, the scores of the antifouling coatings prepared in Examples 1-5 of the present invention are all above 85 points, which are much higher than those in Comparative Examples 1-3, which comprehensively reflects the advantages of the antifouling coatings prepared in Examples 1-5 in antifouling.
[0160] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a transparent marine antifouling coating with high mechanical stability, characterized in that: The preparation method comprises: (I) dispersing phosphorylated nanocellulose in ethanol to obtain a cellulose dispersion, adding 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid to the cellulose dispersion, mixing and stirring, and heating to react, and after the reaction is completed, rotary evaporation is performed to obtain hydrophobically modified nanocellulose; (II) dissolving eugenol and a chain extender in a solvent, mixing and stirring at low temperature to obtain a mixed solution, adding methacryloyl chloride to the mixed solution for reaction, and filtering, adsorbing and evaporating after the reaction to obtain eugenol methacrylate monomer; (III) dropping the eugenol methacrylate monomer, acrylate monomer and initiator obtained in step (II) into a solvent, mixing, stirring and heating to react, thereby obtaining an acrylic acid-eugenol copolymer; (IV) The hydrophobically modified nanocellulose obtained in step (I) and the acrylic acid-eugenol copolymer obtained in step (III) are uniformly mixed to obtain a coating liquid, the coating liquid is applied to the surface of a substrate, and after drying, the transparent marine antifouling coating with high mechanical stability is obtained on the surface of the substrate.
2. The transparent marine antifouling coating with high mechanical stability according to claim 1, characterized in that In step (I), the solid content of the phosphorylated nanocellulose is 0.1 to 1 wt %; The ratio of the phosphorylated nanocellulose to ethanol is 1 g: (20-30) mL; The mass ratio of phosphorylated nanocellulose, 3-glycidyloxypropyltrimethoxysilane, methyltrimethoxysilane and dilute hydrochloric acid in the cellulose dispersion is (1-10):(15-40):(5-20):(0.1-1); The mass fraction of the dilute hydrochloric acid is 5-8wt%.
3. The transparent marine antifouling coating with high mechanical stability according to claim 1, characterized in that In step (I), the heating temperature is 60-70°C; The heating time is 6 to 12 hours; The temperature of the rotary evaporation is 60-90°C; The rotary evaporation time is 3 to 6 hours.
4. The transparent marine antifouling coating with high mechanical stability according to claim 1, characterized in that In step (II), the mass ratio of the eugenol to the solvent is 1:(5-10); The temperature of mixing and stirring the eugenol, the chain extender and the solvent is 3 to 8° C.; The mixing and stirring time of the eugenol, the chain extender and the solvent is 0.5 to 1 hour; The chain extender includes triethylamine; The solvent includes any one of butanone, tetrahydrofuran, benzene, toluene, xylene, chloroform, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide, or a combination of at least two thereof.
5. The transparent marine antifouling coating with high mechanical stability according to claim 1, characterized in that In step (II), the molar ratio of the eugenol, the chain extender and the methacryloyl chloride is 1:(1-1.5):1; The reaction time of the methacryloyl chloride and the mixed solution is 20 to 25 hours; The reaction temperature of the methacryloyl chloride and the mixed solution is 20 to 30° C.; The adsorption process uses cationic adsorption resin.
6. The transparent marine antifouling coating with high mechanical stability according to claim 1, characterized in that In step (III), the acrylate monomers include methyl methacrylate, butyl acrylate and triisopropylsilyl methacrylate; The mass ratio of the eugenol methacrylate monomer, the methyl methacrylate, the butyl acrylate, the triisopropylsilyl methacrylate, the initiator and the solvent is (1-10):(20-60):(10-50):(10-50):(1-5):100; The dripping rate of the eugenol methacrylate monomer, the acrylate monomer and the initiator is 20 to 30 mL / min; Before dripping the eugenol methacrylate monomer, the acrylate monomer and the initiator, blowing nitrogen on the solvent for 30 to 40 minutes; The initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, diisopropylbenzene peroxide or dimethyl azobisisobutyrate or a combination of at least two thereof; The solvent includes any one of butanone, tetrahydrofuran, benzene, toluene, xylene, chloroform, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide, or a combination of at least two thereof.
7. The transparent marine antifouling coating with high mechanical stability according to claim 1, characterized in that In step (III), the heating temperature for mixing and stirring the eugenol methacrylate monomer, the acrylate monomer, the initiator and the solvent is 80 to 90° C.; The heating time for mixing and stirring the eugenol methacrylate monomer, the acrylate monomer, the initiator and the solvent is 3 to 8 hours.
8. The transparent marine antifouling coating with high mechanical stability according to claim 1, characterized in that In step (IV), the mass ratio of the hydrophobically modified nanocellulose to the acrylic acid-eugenol copolymer is (5-20):100; The coating method is spraying, scraping, dripping or brushing; The coating thickness of the coating liquid is 50 to 200 μm; The material of the substrate is iron, aluminum, copper or glass; The drying temperature is 20-30°C; The drying time is 4 to 8 hours.
9. A transparent marine antifouling coating with high mechanical stability prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The transparent marine antifouling coating includes hydrophobically modified nanocellulose and acrylic acid-eugenol copolymer.
10. Use of a transparent marine antifouling coating with high mechanical stability as claimed in claim 9, characterized in that: The transparent marine antifouling coating with high mechanical stability is used for marine optical instruments.
Citation Information
Patent Citations
Antibiotic environmentally-friendly film and production method thereof
CN105925175A
Preparation method of marine anti-corrosive coating
CN112812658A
Nanocellulose composite antifouling coating and preparation method thereof
CN114891400A
Eugenol ester-based methacrylic acid fluorine self-polishing antifouling resin and preparation method thereof
CN115197360A
Transparent self-lubricating organic silicon hybrid antifouling coating with negative electricity on surface and preparation method of transparent self-lubricating organic silicon hybrid antifouling coating
CN117126604A
Cited By
High-solid bio-based acrylate coating and preparation method thereof
CN121249226A
A high solids bio-based acrylate coating and method of making the same
CN121249226B